The Homeland as a Moral Horizon: Philosophical Reflections on Return Migration and Identity Among Repatriated Kazakhs - Aljanova, N.K.; Zhumashova, Zh.; Alibayeva, I.; Mukan, N. (Karagandy University of the name of acad. E.A. Buketov, 2025)
This article explores ethnic return migration to Kazakhstan through a moral-philosophical lens, focusing on the lived experiences of Qandas — ethnic Kazakhs returning from China, Mongolia, and Uzbekistan. While previous research has examined policy frameworks and integration challenges, this study reinterprets return as an ethical and existential process. Drawing on Heidegger’s concepts of dwelling and being-at-home, and the notion of moral geography, we argue that repatriation is experienced as a striving toward a moral horizon rather than a mere relocation. Through narrative interviews with returnees, we reveal how ancestral land is imagined not only as a birthplace but as a space of obligation, memory, and identity reconstruction. Yet returnees often face exclusion and dissonance, complicating state narratives of national restoration. By bridging migration studies, moral philosophy, and phenomenology, this paper illuminates how return becomes an ongoing ethical negotiation of belonging, recognition, and self-becoming in post-Soviet Kazakhstan.
Keywords: belonging; post-Soviet identity; phenomenology; narrative identity; moral horizon; Kazakhstan; repatriation; moral geography; Ethnic return migration